Secondary caries risk of different adhesive strategies and restorative materials in permanent teeth: Systematic review and network meta-analysis. (January 2021) - Askar, Haitham; Krois, Joachim; Göstemeyer, Gerd; Schwendicke, Falk
Abstract: Objectives: Secondary caries is a major long-term complication of dental restorations. Different adhesive strategies and restorative materials may affect secondary caries risk. We aimed to systematically review and synthesize the secondary caries risk of different adhesive strategies and restorative materials. Sources: Medline via PubMed 01/2005-10/2019. Study selection: Randomized controlled studies with minimum 2 years follow-up, comparing different adhesive strategies and/or restorative materials in permanent teeth were included. Our outcome was the occurrence of secondary caries. Bayesian pairwise and network-meta-analysis were conducted. Data: We included 50 trials; 19 assessing secondary caries depending on different adhesive strategies, 31 on restorative materials. Studies were published between 2005 and 2017, largely of unclear risk of bias, and included a mean of 40 (range: 8–90) participants and 46 (range: 14–200) placed restorations. Mean follow-up was 43 (range: 24–180) months. Secondary caries was a rare event; the majority of studies did not find any lesions. Network meta-analysis found great uncertainty. 3-step etch-and-rinse adhesives showed the lowest risk of secondary caries, 2-step etch-and-rinse the highest. For restorative materials, resin-modified glass ionomer showed the lowest risk of secondary caries. Most resin composites showed similar risks. Conclusion: Data from randomized trials comparing different adhesive strategies or restorative materials are extremely scarce. The differences between materials were limited over the observational period of the included studies. The yielded rankings should be interpreted with caution. Clinical significance: Despite often claimed to be a major complication of restorations, there is surprisingly little data on secondary caries from randomized trials. Longer-term studies may be needed to identify differences in secondary caries risk between materials.